2021
DOI: 10.1186/s40510-020-00348-y
|View full text |Cite
|
Sign up to set email alerts
|

Author self-citation in orthodontics is associated with author origin and gender

Abstract: Background The aims of this bibliometric study were to determine author self-citation trends in high-impact orthodontic literature and to investigate possible association between self-citation and publication characteristics. Methods Six orthodontic journals with the highest impact factor as ranked by 2017 Journal Citation Reports were screened for a full publication year (2018) for original research articles, reviews, and case reports. Eligible ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…It is not uncommon for researchers who focus on a specific field to self-cite at all levels of publication, particularly if they have been productive in their field for a while ( Livas et al, 2021 ). Excessive and superfluous self-citations are inappropriate since they artificially inflate citation-based metrics and self-promotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not uncommon for researchers who focus on a specific field to self-cite at all levels of publication, particularly if they have been productive in their field for a while ( Livas et al, 2021 ). Excessive and superfluous self-citations are inappropriate since they artificially inflate citation-based metrics and self-promotion.…”
Section: Discussionmentioning
confidence: 99%
“…In the early years from 2011 to 2013, UC research began to focus on (Actis et al, 2019) cystic fibrosis, asthma, breast cancer, and osteoporosis (Kaplan, 2015); primary sclerosing cholangitis, rheumatoid arthritis, systemic lupus erythematosus, and ankylosing spondylitis (Wilks, 1859); celiac disease, pouchitis, and familial adenomatous polyposis (Viola et al, 2021); abnormal motility, colonic permeability, and enteric nervous system (Nguyen et al, 2018); adipose tissue (Lucaciu et al, 2021); epidemiology, gene polymorphism, susceptibility loci, drug delivery, and activity index (Connelly et al, 2016); dextran sulfate sodium (DSS) and acetic acid (Schöffel et al, 2021); guinea pig (Schöffel et al, 2016); N-acetylcysteine, fish oil, and vitamin D (Chen, 2006); 5-aminosalicylic acid (5-ASA), sulfasalazine, olsalazine, and chitosan (Van Eck and Waltman, 2010); cyclosporin, 6-mercaptopurine, methotrexate, and azathioprine (Aksnes, 2003); certolizumab pegol, infliximab, etanercept, adalimumab, and tacrolimus (Bardeesi et al, 2021); Adacolumn, leukocytapheresis, and apheresis (Freeman, 1977); probiotics, antibiotic therapy, curcumin, traditional Chinese medicine, and electroacupuncture (Cobo et al, 2011); colectomy, ileostomy, and ileal pouch-anal anastomosis; (Kessler, 1963); liver transplantation (Marshakova, 1973); confocal laser endomicroscopy and PillCam colon capsule endoscopy (Small, 1973); C-reactive protein, lactoferrin, and fecal calprotectin (Sandborn et al, 2012a); E-cadherin (Sandborn et al, 2017); Epstein-Barr virus and cytomegalovirus infection (Feagan et al, 2013); Helicobacter pylori, gut microbiota, Escherichia coli, and Clostridium difficile infection (Kleinberg, 2003); short-chain fatty acids, butyrate, and bile acid (Cohen et al, 2010); innate immunity (Ng et al, 2017); regulatory T (T reg ) cell, T helper 17 (Th17) cell, natural killer T cell, and mast cell (Burisch et al, 2020); enterochromaffin cell (Livas et al, 2021); antineutrophil cytoplasmic antibody and anti-Saccharomyces cerevisiae antibody (Glänzel and Thijs, 2004); angiogenesis...…”
Section: Keyword Analysismentioning
confidence: 99%
“…The studies investigating the association between author self-citations and the type and topic of the studies revealed conflicting results in the literature. Livas et al ( 7 ) screened six orthodontic journals with the highest impact factor and found that there was no association between self-citation counts and the type and topic of the studies. However, Tolisano et al ( 17 ) reported that original articles had a significantly higher author self-citation rate, whereas no difference was found among the otolaryngological study topics.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises multiple subtypes that are ascribed for authors, journals, institutions, countries, and languages ( 6 ). Self-citations are likely to be an inevitable entity for productive researchers especially focus on a specific field since they have a higher probability to cite their own papers ( 7 ). Also, self-citations have multiple benefits since they enable authors to expand earlier hypotheses, refer to the established methodology and utilize them for further investigations ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation